Better, faster detection of AFM1 contamination in milk. (Research'eu results magazine)
A breakthrough in the dairy industry has been achieved with the development of new high-tech devices for improving quality control, particularly regarding contamination by the fungal toxicant aflatoxin M1 (AFM1).